Чисельна реалізація однорівневого МСЕРЗ (FETI) методу для плоскої задачі теорії пружності - Дияк, І.І.; Заяць, М.В.; Макар, І.Г. (Фізико-механічний інститут ім. Г.В. Карпенка НАН України, 2010)
Finite Element Method is most widely used to solve boundary value problems. However in the case of domains with complicated geometry, inhomogeneous and large-scale problems some special approaches are needed. The domain decomposition approach for parallel finite element solution of the problem of the theory of elasticity is presented in this study. The computational results of the investigation of numerical efficiency of the developed algorithm are given.